Magnetoviscous effect of ferrite-based magnetic fluid for EOR application - Latiff, N.R.A. (American Institute of Physics Inc., 2016)
Magnetic fluid is proposed as a substitute for the application of polymer solution as a means to recover the residual oil left in the bypassed region in oil reservoirs. When subjected to magnetic field, the viscosity of magnetic fluids increases and enable flow control. In this study, the response of magnetic nanofluid with the applied magnetic field was observed as a function of shear rate. Two types of samples, namely magnetite and cobalt ferrite of 0.1 w/v of different polydispersity index, saturation magnetization and mean hydrodynamic particle size were used. The strength of the applied magnetic field was also varied to investigate the effect of magnetic field strength on the viscosity enhancement of magnetic fluid. Shear dependence response of the magnetic fluid exhibit non-Newtonian behavior when magnetic field of 20 to 40 mT was applied. Viscosity of the magnetic fluid reduced with increasing shear rates, showing shear thinning behavior. At a particular shear rate, viscosity remains constant when the strength of magnetic field increases indicating saturation in chain length even at low field. Magnetoviscous effect (MVE) is calculated as an indicator for a viscosity gain magnitude when magnetic field is applied. Cobalt ferrite sample shows larger MVE compared to magnetite that may be attributed to the higher polydispersity index. In conclusion, particle size distribution is the most dominant factor affecting MVE of the dilute magnetic fluid when magnetic field is applied. Â© 2016 Author(s).